2001
DOI: 10.1021/jp012220k
|View full text |Cite
|
Sign up to set email alerts
|

Electron Paramagnetic Resonance Study of the Dynamics of H and D Atoms Trapped in Substituted Silasesquioxane Cages

Abstract: The hyperfine coupling (hfc) constants, A, and the g-factors of hydrogen isotopes confined in silasesquioxane (R 8 Si 8 O 12 ) cages show significant deviations from the free-particle vacuum value thus revealing the influence of the environment on the wave function of the trapped atom. Accurate measurements of the hfc constants in the temperature range of 5-300 K show a strong isotope effect, different substituents on the cage corners having a clear influence on both static and dynamic cage effects. Deviations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 19 publications
8
30
0
Order By: Relevance
“…To reduce the impact of the error, we added the deviation g Li,tm – g Li to g tm and averaged over several measurements. The final analysis gave g = 2.00294(3) and A = 1413.7(1) MHz, practically identical to the literature values for H in other octaalkylsilsesquioxane hosts [39]. The largest source of uncertainty are the determination of the line centers, the positioning of the teslameter probe in the cavity, and instrumental drifts in the time between spectral acquisitions and teslameter calibrations.…”
Section: Resultssupporting
confidence: 79%
“…To reduce the impact of the error, we added the deviation g Li,tm – g Li to g tm and averaged over several measurements. The final analysis gave g = 2.00294(3) and A = 1413.7(1) MHz, practically identical to the literature values for H in other octaalkylsilsesquioxane hosts [39]. The largest source of uncertainty are the determination of the line centers, the positioning of the teslameter probe in the cavity, and instrumental drifts in the time between spectral acquisitions and teslameter calibrations.…”
Section: Resultssupporting
confidence: 79%
“…Moreover, Roduner et al [14] studied the effects of substitution on the hfs of hydrogen and deuterium in D4R. The temperature dependence has been determined for hydrogen and deuterium in four different cages, HT 8, MeT s, EtT s, and QsMs and the ratios of the hfs constants in the cage to that in vacuum at 0 K were estimated (Table 1) [14]. These ratios appear to correlate with the group electronegativities, which suggests spin delocalization to cage wave functions.…”
Section: Hyperfine Splitting Constantsmentioning
confidence: 99%
“…Roduner and co-workers [14] studied the dependence of the g-values on the temperature and terminal substituents and found that the g-value does not depend on the temperature, but does vary from 2.00273 to 2.00306 when changing the terminal substituents.…”
Section: The G-values Of the Trapped Hydrogenmentioning
confidence: 99%
See 2 more Smart Citations